A luminescent lanthanide approach towards direct visualization of primary cilia in living cells. Issue 52 (19th June 2017) - Li, Hongguang; Lan, Rongfeng; Chan, Chi-Fai; Bao, Guochen; Xie, Chen; Chu, Pak-Ho; Tai, William C. S.; Zha, Shuai; Zhang, Jing-Xiang; Wong, Ka-Leung
Abstract : A simple and direct imaging tool (HGEu001 ) for primary cilia based on long-lived europium luminescence is firstly presented. Abstract : We report a direct imaging tool, HGEu001, for primary cilia in living cells, which is specific, and based on the UV light or near infrared laser ( via two-photon excitation) induced long-lived europium luminescence.